2014
DOI: 10.1310/tsr2105-400
|View full text |Cite
|
Sign up to set email alerts
|

Visual Daily Functioning of Chronic Stroke Patients Assessed by Goal Attainment Scaling After Visual Restorative Training: An Explorative Study

Abstract: Visual restorative function training does not only lead to visual field enlargement, as assessed with dynamic Goldmann perimetry, but it may also lead to a subjective improvement of daily visual functioning as evaluated by means of GAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Only the compensation method resulted in improvements in reading performance ( p = .016) and visual conjunction search ( p = .001), being considered the treatment of choice for the neglect (Mödden et al, 2012). Bergsma and colleagues (2014) also showed the efficacy of visual restoration in visual field enlargement ( p < .005).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Only the compensation method resulted in improvements in reading performance ( p = .016) and visual conjunction search ( p = .001), being considered the treatment of choice for the neglect (Mödden et al, 2012). Bergsma and colleagues (2014) also showed the efficacy of visual restoration in visual field enlargement ( p < .005).…”
Section: Resultsmentioning
confidence: 84%
“…Concerning restoration, Mödden and collaborators (2012) showed different colored targets at different positions from the visual field limit without ocular movement. Bergsma and colleagues (2014) used a computerized program for visual restoration.…”
Section: Resultsmentioning
confidence: 99%
“…So far, we have focused on the perimetric changes, but the ultimate goal of rehabilitation is an improvement of daily life measures. Previous work in chronic patients reported significant improvement following training using questionnaires ( 30 , 31 ) reading speed ( 9 , 10 ) and eye saccades during a driving test ( 28 ). Here, we monitored two parameters: reading speed increase and success in achieving improvement on visually affected tasks of daily living (GAS).…”
Section: Discussionmentioning
confidence: 97%
“…Only one previous study reported GAS improvements after visual training in chronic hemianopia patients ( 31 ), but GAS improvement and field improvement appeared unrelated, possibly because goals had not been set realistically (e.g., peripheral recovery goals in hemianopia patients with a small macula sparing).…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, only 8% of patients reported this symptom. These disorders can be treated through training to restore visual function, not only to increase visual field capabilities but also to subjectively improve regular visual functions 40 .…”
Section: Discussionmentioning
confidence: 99%